Polarographic Studies of Mixed Ligand Complexes Of Copper Cadaverine with Some Carboxylic Acids - Kumar Lohiya, Rajendra; Lal Prathar, Panna; Singh, R.V.; Mukerji, S.K. (Asian Journal of Chemistry, 2010)
Mixed ligand complexes of Cu(II) with cadaverine and carboxylic acids including adipic acid, succinic acid, maleic acid, malonic acid and phthalic acid have been studied polarographically. Formation constants of these complexes have been evaluated using McMaster and Schaap technique. The log K values for Cu-Cdv-Phth, Cu-Cdv-Mal, Cu-Cdv-Malo, Cu-Cdv-Succ and Cu-Cdv-Adp systems are -3.02, -3.50, -3.11, -3.67 and -2.51, respectively. The pH's of the solutions were kept at 7.9, 8.6, 8.2, 8.3 and 8.2 for the Malo- Cdv, ,Mal-Cdv, Adp-Cdv, Succ-Cdv, Phth-Cdv systems, respectively.